La relazione fra i concetti di potere temporale e di potere spirituale nella tradizione cristiana fino al secolo XIV - Tabacco, Giovanni (Reti Medievali E-Book, 2011)
Give to Caesar what belongs to Caesar, to God what belongs to God: starting from the challenging interpretation of the famous passage from the Gospel of Matthew (22:21), the here presented monograph by Giovanni Tabacco goes through the stages that defined and shaped the relations between civil and religious powers in the West throughout the medieval millennium. Published for the first time in 1950 by the Faculty of Letters and Philosophy of the University of Turin, the study of the great medievalist belongs to the never forgotten "classics" of Italian medieval historiography. The monograph is preceded by three introductory interventions (Laura Gaffuri, Giovanni Miccoli, Gian Maria Varanini) dedicated to the meaning and relevance of Giovanni Tabacco's reflection, and to the important period of studies that, between the early twentieth century and the immediate second postwar period, questioned the origins of church-state relations.